Novel structure of the recA locus of Mycobacterium tuberculosis implies processing of the gene product. - Davis, E O (1991)
A fragment of Mycobacterium tuberculosis DNA containing recA-like sequences was identified by hybridization with the Escherichia coli recA gene and cloned. Although no expression was detected from its own promoter in E. coli, expression from a vector promoter partially complemented E. coli recA mutants for recombination, DNA repair, and mutagenesis, but not for induction of phage lambda. This clone produced a protein which cross-reacts with antisera raised against the E. coli RecA protein and was approximately the same size. However, the nucleotide sequence of the cloned fragment revealed the presence of an open reading frame for a protein about twice the size of other RecA proteins and the cloned product detected by Western blotting (immunoblotting). The predicted M. tuberculosis RecA protein sequence was homologous with RecA sequences from other bacteria, but this homology was not dispersed; rather it was localized to the first 254 and the last 96 amino acids, with the intervening 440 amino acids being unrelated. Furthermore, the junctions of homology were in register with the uninterrupted sequence of the E. coli RecA protein. Identical restriction fragments were found in the genomic DNAs of M. tuberculosis H37Rv and H37Ra and of M. bovis BCG. It is concluded that the ancestral recA gene of these species diversified via an insertional mutation of at least 1,320 bp of DNA. Possible processing mechanisms for synthesizing a normal-size RecA protein from this elongated sequence are discussed.